Daxx mediates SUMO-dependent transcriptional control and subnuclear compartmentalization. (23rd November 2007) - Shih, H.-M.; Chang, C.-C.; Kuo, H.-Y.; Lin, D.-Y.
Abstract : SUMO (small ubiquitin-related modifier) modification is emerging as an important post-translational control in transcription. In general, SUMO modification is associated with transcriptional repression. Although many SUMO-modified transcription factors and co-activators have been identified, little is known about the mechanism underlying SUMOylation-elicited transcriptional repression. Here, we summarize that SUMO modification of transcription factors such as androgen receptor, glucocorticoid receptor, Smad4 and CBP [CREB (cAMP-response-element-binding protein)-binding protein] co-activator results in the recruitment of a transcriptional co-repressor Daxx, thereby causing transcriptional repression. Such a SUMO-dependent recruitment of Daxx is mediated by the interaction between the SUMO moiety of SUMOylated factors and Daxx SUMO-interacting motif. Interestingly, the transrepression effect of Daxx on these SUMOylated transcription factors can be relieved by SUMOylated PML (promyelocytic leukaemia) via altering Daxx partition from the targeted gene promoter to PML nuclear bodies. Because Daxx SUMO-interacting motif is a common binding site for SUMOylated factors, a model of competition for Daxx recruitment between SUMOylated PML and SUMOylated transcription factors was proposed. Together, our findings strongly suggest that Daxx functions as a SUMO reader in the SUMO-dependent regulation of transcription and subnuclear compartmentalization.